A nutritional supplement containing zinc during preconception and pregnancy increases human milk zinc concentrations - Han, Soo Min; Devaraj, Surabhi; Derraik, José G. B.; Vickers, Mark H.; Huang, Fang; Dubascoux, Stephane; Godfrey, Keith M.; Chan, Shiao-Yng; Pang, Wei Wei; Thakkar, Sagar K.; Cutfield, Wayne S.; , NiPPeR Study Group; et al. (Frontiers in Nutrition, 2023)
During pregnancy and lactation minerals such as zinc are required to support maternal and infant health. Zinc is involved in various cellular processes, with requirements increasing in pregnancy and lactation. In the setting of a randomised trial, we investigated the effects on human milk (HM) zinc concentrations of a micronutrient containing supplement including zinc in the intervention (but not control) group, started preconception and taken throughout pregnancy until birth. Additionally, we characterised longitudinal changes in HM concentrations of zinc and other minerals (calcium, copper, iodine, iron, magnesium, manganese, phosphorus, potassium, selenium and sodium). HM samples were collected across 7 time points from 1 week to 12 months from lactating mothers from Singapore (n=158) and New Zealand (n=180). HM minerals were quantified using sector field inductively coupled plasma mass spectrometry. Potential intervention effects on HM mineral concentrations were assessed using linear mixed models with a repeated measures design and time-weighted area-under-the-curve analysis. Over the first 3 months of lactation, HM zinc concentrations were 11% higher in the intervention group compared to the control group (p=0.021). Higher HM zinc concentrations were most evident at 6 weeks of lactation. The intervention had no effect on HM concentrations of other minerals, which were not differently supplemented to the control and intervention groups. Temporal changes in HM minerals over 12 months of lactation were studied in the New Zealand mothers; HM zinc and copper concentrations progressively decreased throughout 12 months, while iron, potassium, sodium and phosphorus decreased until 6 months then plateaued. HM calcium and magnesium initially increased in early lactation and iodine remained relatively constant throughout 12 months. HM manganese and selenium fell over the initial months of lactation, with a nadir at 6 months, and increased thereafter. The contrasting patterns of changes in HM mineral concentrations during lactation may reflect different absorption needs and roles at different stages of infancy. Overall, this study indicates that HM zinc concentrations are influenced by maternal supplementation during preconception and pregnancy. Further studies are required to understand the associations between HM zinc and other minerals and both short- and long-term offspring outcomes.